2009
DOI: 10.3168/jds.2008-1495
|View full text |Cite
|
Sign up to set email alerts
|

Developmental competence of bovine embryos from heat-stressed ova

Abstract: Because multiple ovulation embryo transfer procedures are occasionally performed in cows experiencing heat stress, the goal of this study was to assess the developmental competence of otherwise morphologically normal embryos from heat-stressed ova. To this end, the ability of compact morulae from heat-stressed and non-heat-stressed bovine ova to undergo blastocyst development after culture at 38.5 or 41.0 degrees C was examined. It was hypothesized that heat-induced perturbations in the ooplasm carry over to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
4
28
0
4
Order By: Relevance
“…In vitro maturation, fertilization (IVF), and culture of resultant embryos were performed as previously described [23,25,26]. Briefly, cumulus-oocyte complexes were matured in Medium-199 containing Earle's salts, 10% fetal bovine serum, 50.0 μg/ml gentamicin, 5.0 μg/ml FSH, 0.2 mM Na pyruvate, and 2 mM Lglutamine) in a 5.5% CO2 humidified environment.…”
Section: General Methods For Sample Processing and Rna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro maturation, fertilization (IVF), and culture of resultant embryos were performed as previously described [23,25,26]. Briefly, cumulus-oocyte complexes were matured in Medium-199 containing Earle's salts, 10% fetal bovine serum, 50.0 μg/ml gentamicin, 5.0 μg/ml FSH, 0.2 mM Na pyruvate, and 2 mM Lglutamine) in a 5.5% CO2 humidified environment.…”
Section: General Methods For Sample Processing and Rna Extractionmentioning
confidence: 99%
“…In summary, results described herein document the extent to which heat-induced perturbations occurring at the molecular level during meiotic maturation affect later stage embryos after fertilization. Previous efforts of Edwards et al [26] demonstrating that later stage embryos from heat-stressed oocytes are not as developmentally-competent as those from nonheat-stressed oocytes suggests that heat-induced alterations in RNA may not be without consequence. Demonstrated differences occurring at the molecular level in embryos from heat-stressed oocytes emphasizes the importance of minimizing stress exposure during meiotic maturation.…”
mentioning
confidence: 99%
“…On the other hand, some findings provided evidence for bovine HSO to mature faster than non-heat-stressed counterparts (Edwards et al, 2005;Schrock et al, 2007; Andreu- Vazquez et al, 2010). In agreement with our results, oocytes heat-stressed during the germinal vesicle stage (bovine: Payton et al, 2004;mouse: LaRosa and Downs, 2007) or during maturation (bovine: Ju et al, 2005;Schrock et al, 2007;Edwards et al, 2009;Zhandi et al, 2009;Rispoli et al, 2011;Payton et al, 2011) have shown competence in overcoming the first cellular division similar to that found in non-HSO. In addition, we observed that HS treatment improved the ability of the oocytes to form blastocysts.…”
Section: Discussionsupporting
confidence: 81%
“…It was reported that high temperatures decrease the oocyte maturation and reduces the number of embryos that cleave into two cells (Lenz et al, 1983;Rivera and Hansen, 2001). Heat stress was also reported to negatively affect the fertilization and embryonic development both in vitro and in vivo (Al-Katanani et al, 2002;Sartori et al, 2002;Hansen, 2007;Edwards et al, 2009); however, another study indicated no change during the summer (Ryan et al, 1993). Cerri et al (2009a,b,c) reported that the season affected the embryo development and number.…”
Section: Effect Of Choice Of Month Of Treatmentmentioning
confidence: 96%